Discontinuation Rate of Lurasidone and Quetiapine Extended Release in Bipolar Depression - Kishi, Taro; Sakuma, Kenji; Hamanaka, Shun; Nishii, Yasufumi; Iwata, Nakao (Pharmacopsychiatry, 2024)
Introduction Lurasidone (LUR) was compared with quetiapine extended release (QUE-ER) regarding 1-year discontinuation in patients with bipolar depression (n=317).Methods This is a retrospective cohort study.Results Although the time to all-cause discontinuation was estimated using the Kaplan–Meier survival curve with log-rank tests to compare treatment groups, no difference was found (p=0.317). The Cox proportional hazard model revealed that only the presence of adverse events (AEs) is associated with increased treatment discontinuation (p<0.0001). The most common AEs were akathisia for LUR (17.7%) and somnolence for QUE-ER (34.7%). In other Cox models divided by LUR or QUE-ER, the presence of akathisia or somnolence was associated with increased LUR (p=0.0205) or QUE-ER (p<0.0001) discontinuation, respectively.Discussion The acceptability of both antipsychotics to bipolar depression in clinical practice may be similar. However, specific AEs for each antipsychotic (LUR: akathisia and QUE-ER: somnolence) were associated with high treatment discontinuation.
Keywords: lurasidone; quetiapine extended release; bipolar depression